Bandwidth-aware Peer-to-Peer 3D streaming. (12th November 2010) - Chien, Chien-Hao; Hu, Shun-Yun; Jiang, Jehn-Ruey; Cheng, Chuan-Wei
This paper proposes Bandwidth-Aware Peer Selection (BAPS), a peer selection strategy that improves the bandwidth utilisation for Peer-to-Peer (P2P) 3D streaming in a real-time Virtual Environment (VE). BAPS enhances Flowing Level-of-Details (FLoD), another P2P 3D streaming scheme, by avoiding request contention and peer overloading. We compare BAPS with FLoDs strategies that select from only peers within the Area of Interest (AOI) as data sources and do not consider peer bandwidth capacity. Our evaluation shows that BAPS achieves better performance in general, and maintains a stable minimal Quality of Service (QoS) for streaming, which is important for commercial applications.